2009
DOI: 10.1016/j.neurobiolaging.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins, neuropathology and cognitive status in the oldest-old

Abstract: An increasing number of individuals in our population are surviving to over 90 years and a subset is at risk for developing dementia. However, senile plaque and neurofibrillary tangle pathology do not consistently differentiate individuals with and without dementia. Synaptic protein loss is a feature of aging and dementia and may dissociate 90+ individuals with and without dementia. Synaptophysin (SYN), postsynaptic density 95 (PSD-95) and growth-associated protein 43 (GAP-43) were studied in the frontal corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
89
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 56 publications
14
89
1
Order By: Relevance
“…29 The other study reported that in the frontal cortex of old-older normal controls with AD pathology, equivalent to our ASYMAD group, synaptophysin, a presynaptic marker, is enhanced. 30 An alternative explanation, based on functional neuroimaging studies, 31,32 could be that in ASYMAD, some neurons and circuits are irreversibly damaged by AD pathology, and different and compensatory circuits become operative based on different stages of disease. Consequently, the circuitry of the cerebral Figure 1 Cell body, nuclear, and nucleolar markers for morphometric measurements (A) Large coronal section of a formalin-fixed brain of a control subject (left hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…29 The other study reported that in the frontal cortex of old-older normal controls with AD pathology, equivalent to our ASYMAD group, synaptophysin, a presynaptic marker, is enhanced. 30 An alternative explanation, based on functional neuroimaging studies, 31,32 could be that in ASYMAD, some neurons and circuits are irreversibly damaged by AD pathology, and different and compensatory circuits become operative based on different stages of disease. Consequently, the circuitry of the cerebral Figure 1 Cell body, nuclear, and nucleolar markers for morphometric measurements (A) Large coronal section of a formalin-fixed brain of a control subject (left hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…) or their components (synapses 8,9 ) in key locations. This approach allows collection of neuronal and pathologic data from the same brain regions, facilitating examination of their conjoint correlations with cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been considered, such as relatively intact synaptic integrity [36] , larger brain size [7] and higher efficiency in clearing soluble ␤ -amyloid relative to 4 [37,38] . The latter possible mechanism is helpful in explaining the difference in MRI measures between the 2 and 4 carriers.…”
Section: Discussionmentioning
confidence: 99%